Dynamic stability assessment of the Iraqi power system network - Hassan, L.H.; Moghavvemi, M.; Mohamed, H.A.F. (2009)
This paper assesses the dynamic stability of the Iraqi National Super Grid System (INSGS) using the Eigenvalue analysis method. A two-axis dynamic model is proposed to study electromechanical oscillations. The mathematical model of the power system is formed after establishing the initial conditions. Then, the high order nonlinear differential equations are linearized by using the perturbation method. Here, the machine speed equations of the system are derived and the eigenvalues are obtained from the state matrix. In addition, the contributions of machines to a particular eigenvalue are computed.